Isolated melanoma metastasis in a patient with large congenital nevus without detectable primary melanoma: a case report and review of literature - Pabianek, Marta; Jatczak-Grochala, Ilona; Lesiak, Aleksandra; Narbutt, Joanna; Siekierko, Aleksandra; Stasikowska-Kanicka, Olga; Ciążyńska, Magdalena (Frontiers in Medicine, 2024)
Giant congenital pigmented nevi constitute an extremely diverse group of skin lesions in terms of morphology, which are often associated with many clinical implications such as: development of melanoma or presence of neurocutaneous melanosis, primarily a development of melanoma.We present rare case of a 62-year-old patient with a giant congenital birthmark who reported to oncology department due to a tumor in the lower abdomen detected during an ultrasound examination. Biopsy of the lesion showed the presence of melanoma metastasis. Four independent dermatologists performed a dermoscopic examination of the patient's skin and mucous membranes. In the PET/CT examination, apart from the previously described change in the lower abdomen, no metabolically active foci with features of malignant growth were found. The patient underwent surgical removal of the lesion in the lower abdomen. The postoperative histopathological examination confirmed the presence of metastasis of melanoma of the subcutaneous tissue of the abdomen with no connection to the epidermis. The BRAFV600 mutation was not found in the molecular test.Taking to consideration stage IV R0 melanoma of unknown primary origin, and with stage T0N0M1a, the only adjuvant treatment option in the case of melanoma with distant metastasis after radical resection is treatment with nivolumab. After a rheumatological consultation the patient was qualified for adjuvant treatment with nivolumab.